2019
DOI: 10.15294/dp.v14i1.19226
|View full text |Cite
|
Sign up to set email alerts
|

The Development Assessment Instruments of Higher Order Thinking Skills on Economic Subject

Abstract: This research aims to develop Higher Order Thinking Skills (HOTS) based assessment instruments on economic subjects especially in Basic Competencies 3.4 price and inflation index. This study adopts the development model of Borg & Gall which is limited to five stages of development, namely, data collection, product design, product testing, product analysis and final product revision. This research was conducted on 33 students of Social Eleven One class at Senior High School 1 Cerme. This assessment instrume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 7 publications
2
18
0
6
Order By: Relevance
“…Students must often be faced with exercises working on HOTS questions that are interesting to solve, so that the potential of students increases. In the current 2013 curriculum, while the syllabus serves as a guide in learning activities in schools, the material prepared requires students to have high-level thinking skills [15], and of course the assessment must adjust to the ability to think at a high level, especially in history learning in high school [16], [17]. The meaning of assessment in the realm of education is to find out the achievement of objectives and the process of learning activities [18], [19], therefore assessment must meet academic requirements as an appropriate assessment carried out in high school.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Students must often be faced with exercises working on HOTS questions that are interesting to solve, so that the potential of students increases. In the current 2013 curriculum, while the syllabus serves as a guide in learning activities in schools, the material prepared requires students to have high-level thinking skills [15], and of course the assessment must adjust to the ability to think at a high level, especially in history learning in high school [16], [17]. The meaning of assessment in the realm of education is to find out the achievement of objectives and the process of learning activities [18], [19], therefore assessment must meet academic requirements as an appropriate assessment carried out in high school.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research on higher order thinking skills has been carried out by several researchers who have focused on learning mathematics [30], learning physics [31] and learning history with descriptive questions [17]. Based on previous research studies on the HOTS, researchers found a new aspect of this research is the development of HOTS assessments with multiple choice test questions, especially in assessing the learning of Indonesian history.…”
Section: Introductionmentioning
confidence: 99%
“…Sejalan dengan itu hasil penelitian lain menjelaskan bahwa pembelajaran yang efektif dapat tercipta dengan pemanfaatan teknologi yang memadai dan sesuai dengan tujuan pembelajaran (Albina & Sumagaysay, 2020;Burbules, Fan, & Repp, 2020;Haubold, Mathai, & Pyenson, 2020). Penggunaan evaluasi pendidikan berupa High Order Thinking Skills (HOTS) dapat meningkatkan kemampuan siswa terutama pada aspek kognitif untuk memenuhi tujuan pembelajaran pada bidang ekonomi (Kurniawan & Lestari, 2019).…”
Section: Pendahuluan Latar Belakangunclassified
“…To improve the quality of education, especially in the 21 st Century, students need to develop higherorder thinking skills. Higher order thinking skills can also be trained and developed through classroom learning [19]. Craig [20] suggests that in the 21 st century students will deal with unusual problems, so they must be familiar with activities related to solution to problem.…”
Section: Introductionmentioning
confidence: 99%